Cover Picture: Fine‐Tuning Covalent Inhibition of Bacterial Quorum Sensing (ChemBioChem 9/2016). (3rd May 2016) - Amara, Neri; Gregor, Rachel; Rayo, Josep; Dandela, Rambabu; Daniel, Erik; Liubin, Nina; Willems, H. Marjo E.; Ben‐Zvi, Anat; Krom, Bastiaan P.; Meijler, Michael M.
Abstract : The cover picture shows schematically how the important quorum‐sensing regulator LasR of the human pathogen Pseudomonas aeruginosa can be targeted with tailor‐made covalent probes. A diverse array of electrophile‐containing N‐acylated homoserine lactones was prepared and evaluated for their ability to covalently modify LasR. Striking differences in activity were observed between the halogenated isothiocyanates. More information can be found in the full paper by M. M. Meijler et al onpage 825 in Issue 9, 2016 l. (DOI:10.1002/cbic.201500676 ).